PERAN PELATIHAN TERHADAP KINERJA KARYAWAN (STUDI LITERATUR) - Sukardi, Roy Fransiskus; Kalbuadi, Amiruddin (RJABM (Research Journal of Accounting and Business Management), 2024)
The goals of an organization or company can be achieved if it is supported by employees who have competencies according to the field within the company, therefore employees are an important production factor. Companies need human resources who have competencies according to their fields to run the business in the most effective way. Employees help the company achieve its goals by leading, thinking, and planning. To achieve organizational goals, companies carry out integrated training and education for their employees. One of the efforts made by companies to improve the quality of human resources in the world of work is by providing training. Training is the process of training and equipping employees with skills, knowledge and intellectual abilities. The aim of this literature research is to determine the role of training in improving employee performance using the literature review method. Literature studies are based on searching scientific articles. The research results show that training has an important role in increasing employee competency which will encourage increased employee performance